PENGARUH PEER ATTACHMENT TERHADAP STRES AKADEMIK MAHASISWA PSIKOLOGI KAMPUS V UNP - Oktaviani, Nurul; Humaira, Annisa; Fajarwati, Adinda; Orva Linnisa, Verlin; Ryanto, Syifa; Remaopdea Putri, Hafizah; Putri, Nadya; Br Karo, Nandira; Viska Levindra, Nadia; Arinda Putri, Rolia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of peer attachment on the level of academic stress experienced by undergraduate students of the Psychology program at Padang State University. The method used in this research is a quantitative approach with a correlational design, including statistical analysis to measure the relationship between peer attachment variables and academic stress. The results showed that there was a significant negative relationship between the quality of peer attachment and the level of academic stress. The higher the quality of the relationship, the lower the student's stress level. In addition, other factors such as academic workload can also cause stress. This study highlights the importance of peer emotional support in reducing academic stress and recommends social support-based interventions to address the academic pressure faced by students.